The importance of uptake time in FDG imaging of patients with lymphoma - Dunn, J; Mikhaeel, N; Puri, T; Marsden, P; O'Doherty, M; Barrington, S (Springer Verlag, 2016)
EANM guidance recommends 60 minute uptake for FDG oncology scans, however uptake increases in several tumours beyond 60 minutes. The aim of this study was to determine the time course of FDG uptake in common lymphoma types after injection and how this might affect imaging assessment.